Corrosion survey database (COR SUR)
This database is a collection of the results from numerous literature references reporting the effects of exposing 87 metal and nonmetal materials to over 1500 different exposure media at various temperatures and concentrations resulting in 28,000 pairs of exposed material and medium. The results are presented in searchable tables, and can be browsed by material or exposure medium.